Ultrasensitive therapeutic drug monitoring of methotrexate by a structure-switching aptamer with cascade primer exchange reaction. Issue 2 (19th December 2022) - He, Junqing; Wang, Junyan; Zhang, Min; Shi, Guoyue
Abstract : As a folate antagonist, methotrexate (MTX) has been widely used in clinics with good effects on various tumors and inflammatory diseases. Abstract : As a folate antagonist, methotrexate (MTX) has been widely used in clinics with good effects on various tumors and inflammatory diseases. While the optimum dosage and total body clearance of MTX usually varies between individuals and even low-dose MTX has side effects, high-dose MTX may cause life-threatening side effects. Therefore, a convenient and simple method toward MTX sensing is highly demanded. Herein, we report a highly sensitive and selective method for therapeutic drug monitoring (TMD) of MTX by integrating a highly specific MTX-dependent structure-switching aptamer with a primer exchange reaction-based signal amplification technique. The detection limit is down to 1.7 nM with a linear range from 0.01 to 1 μM in buffer. More importantly, the sensing strategy can effectively detect MTX in a complex bio-environment with a linear response range from 0.05 to 2 μM and a LOD of 12.4 nM in 10% FBS and a range of 0.2 to 5 μM with a LOD of 63.73 nM in 10% whole blood. Considering the high sensitivity and selectivity and good performance in blood, the method reported herein paves a new avenue for the effective determination of MTX in clinics.